Dinamika Kesenjangan Pendapatan dan Tingkat Kemiskinanan di Kota Medan: Analisis Trend Periode 2021 - 2025 - Analia Br Togatorop, Grestin; Regita Cahyani Br Karo Sekali,; Silvia Putriani,; Lokot Muda Harahap, (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2026)
This study is motivated by the importance of understanding the dynamics of poverty and income inequality as key indicators of social welfare in the process of regional economic development. As one of the major economic centers in western Indonesia, Medan City has experienced an economic recovery following the COVID-19 pandemic, which potentially affects the socio-economic conditions of its population. This study aims to analyze the development and trend patterns of poverty levels and income inequality, measured by the Gini Ratio, in Medan City during the period 2021–2025. The study employs a quantitative approach using a descriptive method through trend analysis of secondary data obtained from official publications of Statistics Indonesia (BPS). The results show that the poverty rate in Medan City gradually declined from 8.34 percent in 2021 to 7.25 percent in 2025. During the same period, the Gini Ratio also decreased from 0.402 to 0.305, indicating an improvement in the distribution of income among the population. These findings suggest that the economic recovery in Medan City has not only contributed to poverty reduction but has also been accompanied by a decline in income inequality. This condition indicates that regional economic development in Medan City is gradually moving toward more inclusive economic growth.